Designing of an operational amplifier - Timyati, Firdaus @ Nukha (2008)
Natural signals come in analog forms and these signals are bearing valuable information and need to be processed. An operational amplifier is the most versatile and important building blocks in analog circuit design. Therefore this project is dedicated to designing an operational amplifier and analyzing the properties. The performance is measured based on its DC and small-signal analysis, Schematic of the circuit is drawn using Tanner EDA's S-EditTM. Then T-Spice™ is utilized to simulate the circuit. Output waveform generated by W-edit is used to obtain the DC curve, the Bode plot for magnitude and Bode plot for phase. Additionally, other types of parameters are used for the same circuit. It is found that Level 1 Parameters suits the operational amplifier being designed and it works well as expected. The design gives a 96dB gain. The layout for the whole circuit is done based on MOSIS layout rules using SCN3M technology.